Language-indexed affective-motivational profiles of Japanese major undergraduates: a Q methodology study - Talaibek Musaev; Jamaluddin Aziz; Jamila Mohd (Penerbit Universiti Kebangsaan Malaysia, 2025)
Research on emotions in second-language learning has typically treated affect as a global learner trait and has rarely examined how affective experience is systematically shaped by specific structural and sociopragmatic features of the target language. This study addresses that gap by investigating how affective-motivational configurations in Japanese learning are indexed to distinct linguistic loci: orthographic processing, lexical deployment, clause-level comprehension, and sociopragmatic calibration. Using Q methodology, thirty-three undergraduates majoring in Japanese rank-ordered 45 self-referential statements about concrete linguistic encounters and motivational-evaluative appraisals on a forced quasi-normal distribution. Data were analysed using by-person centroid extraction with varimax rotation and triangulated with post-sort justifications, whereas follow-up interviews were conducted to corroborate interpretations. The analysis reconstructed three structurally independent profiles that together explain 39% of the study-sample variance across three factors. Factor 1 is a Mastery-Oriented Intrinsic Engagement, characterized by translation-free comprehension and orthographic consolidation with minimal social anxiety; Factor 2 is an Affective Overload and Motivational Depletion, marked by linguistic overwhelm under evaluative pressure and depleted persistence; and Factor 3 is a Resilient Persistence with Sociopragmatic Anxiety, exhibiting sustained motivation despite public speaking stress. The findings show how appraisals of control and value are configured around learners' phenomenological encounters with Japanese linguistic features, not only general learning conditions. Overall, the patterns indicate that emotions and motivation in this sample vary with the particular linguistic features engaged rather than reflecting a single global disposition.